E × B flow shear mitigates ballooning-driven edge-localized modes at high collisionality: experiment and simulation. (13th December 2018) - Kong, D.F.; Xu, X.Q.; Diamond, P.H.; Chen, J.G.; Huang, C.B.; Lan, T.; Gao, X.; Li, J.G.
Abstract: By using the specific co-neutral beam injection (co-NBI) and counter-NBI systems on EAST, an alternating flow shear discharge has been obtained to study the impact of the flow shear on ballooning-driven edge localized modes (ELMs) at a fixed high collisionality ( ). The results reveal that the increased flow shear can significantly mitigate ELMs, or even totally suppress ELMs when the shear is large enough. Our simulations with BOUT support the observations on EAST, and further indicate that the increased can both reduce the linear growth rate of the ballooning mode and shorten its growth time (phase coherence time, PCT). The enhanced nonlinear interactions shorten the PCT of the ballooning mode, as validated by the bispectrum study on EAST. All those studies suggest a new way to control ELMs.